Karyotype of the Blastocoel Fluid Derived by Laser-Assisted Hatching Demonstrates a Low Agreement With the Trophectoderm - Wang, Liang; Pang, Wenjuan; Zhang, Yi; Hao, Min; Liu, Yan; Wang, Xiang; Sun, Ningxia (Frontiers in Physiology, 2022)
Objective: The aim of this study is to compare the amplification efficiency and the genomic profiles of blastocoel fluid (BF) derived by laser-assisted hatching and trophectoderm (TE) cells derived from the same blastocyst. Methods: Fifty-four fresh blastocysts underwent shrinkage by laser-assisted hatching, and each BF sample was collected individually. BF and TE cells were retrieved from each blastocyst for chromosome analysis through multiple annealing and looping-based amplification cycles (MALBAC) and next-generation sequencing (NGS). Results: Fifty-four BF samples and 32 TE samples were retrieved for this study. Out of the 54 BF samples, only 35 provided reliable NGS data for comprehensive chromosome analysis (64.8%), while all 32 TE samples did (100%). Finally, there were 23 pairs of BF and TE samples from the same blastocyst. Only 17.4% of the BF-DNA karyotypes were completely agreeable with the TE samples (4/23). Conclusion: BF derived by laser-assisted hatching is easy to operate, and BF-DNA can be successfully amplified and subjected to NGS. Due to the low amplification efficiency and increased discordance with TE, BF does not adequately represent the status of the rest of the blastocyst. The use of BF as a single source of DNA for preimplantation genetic screening is not yet advised.